2018
DOI: 10.2337/dc17-1827
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine in Type 2 Diabetes: Clinical Markers of Insulin Resistance Are Associated With Altered Short- and Long-term Glycemic Response to DPP-4 Inhibitor Therapy

Abstract: Markers of higher insulin resistance are consistently associated with reduced glycemic response to DPP-4 inhibitors. This finding provides a starting point for the application of a precision diabetes approach to DPP-4 inhibitor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 39 publications
(50 reference statements)
6
81
0
Order By: Relevance
“…They replicated the results in United Kingdom electronic health care records showing that higher triglycerides and body mass index were associated with decreased HbA 1c response to DPP‐4 inhibitors, which was totally independent of age, sex, ethnicity, baseline HbA 1c values, duration of diabetes, and estimated glomerular filtration rate . Furthermore, they found that type 2 diabetic patients with obese and hypertriglycaeridemia had less durable response to DPP‐4 inhibitors; relative risk of glycaemic failure (HbA 1c ≥ 8.5%) after 3‐year treatment with DPP‐4 inhibitors was significantly higher in these patients compared with non‐obese and normal triglycaeridemia subjects . Since there was no significant association between markers of insulin resistance and response to GLP‐1 receptor agonists in their cohorts, Dennis et al stated that impaired GLP‐1 secretion, but not reduced GLP‐1 receptor expression in islets, would explain the reduced glycaemic response to DPP‐4 inhibitor therapy in insulin‐resistant type 2 diabetic patients.…”
Section: Conflict Of Interestsmentioning
confidence: 58%
See 3 more Smart Citations
“…They replicated the results in United Kingdom electronic health care records showing that higher triglycerides and body mass index were associated with decreased HbA 1c response to DPP‐4 inhibitors, which was totally independent of age, sex, ethnicity, baseline HbA 1c values, duration of diabetes, and estimated glomerular filtration rate . Furthermore, they found that type 2 diabetic patients with obese and hypertriglycaeridemia had less durable response to DPP‐4 inhibitors; relative risk of glycaemic failure (HbA 1c ≥ 8.5%) after 3‐year treatment with DPP‐4 inhibitors was significantly higher in these patients compared with non‐obese and normal triglycaeridemia subjects . Since there was no significant association between markers of insulin resistance and response to GLP‐1 receptor agonists in their cohorts, Dennis et al stated that impaired GLP‐1 secretion, but not reduced GLP‐1 receptor expression in islets, would explain the reduced glycaemic response to DPP‐4 inhibitor therapy in insulin‐resistant type 2 diabetic patients.…”
Section: Conflict Of Interestsmentioning
confidence: 58%
“…Methodological limitations, ecological bias, and unadjusted confounders, such as baseline fasting plasma glucose and HbA 1c values, may account for the discrepant findings. Meanwhile, Dennis et al have recently reported that elevation of markers of insulin resistance, such as higher fasting C‐peptide, HOMA2‐IR, and triglycerides, is associated with reduced 6‐month HbA 1c response to DPP‐4 inhibitor therapy in non‐insulin treated type 2 diabetic patients. They replicated the results in United Kingdom electronic health care records showing that higher triglycerides and body mass index were associated with decreased HbA 1c response to DPP‐4 inhibitors, which was totally independent of age, sex, ethnicity, baseline HbA 1c values, duration of diabetes, and estimated glomerular filtration rate .…”
Section: Conflict Of Interestsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent re‐analysis of the ADOPT study by the MASTERMIND consortium showed that SUs were much more effective than rosiglitazone in non‐obese men. In contrast, obese women responded better over 5 years to rosiglitazone than SUs …”
Section: Sulphonylurea Efficacy and Safetymentioning
confidence: 88%